2016
DOI: 10.1088/0029-5515/57/2/022013
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear modeling of the plasma response to RMPs in ASDEX Upgrade

Abstract: The plasma response to Resonant Magnetic Perturbations (RMPs) in ASDEX Upgrade is modeled with the non-linear resistive MHD code JOREK, using input profiles that match those of the experiments as closely as possible. The RMP configuration for which Edge Localized Modes are best mitigated in experiments is related to the largest edge kink response observed near the X-point in modeling. On the edge resonant surfaces q = m/n, the coupling between the m + 2 kink component and the m resonant component is found to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 49 publications
7
75
0
Order By: Relevance
“…Such a correlation has previously been obtained in the modelling of several tokamak devices 4,7,8,13,25 and will be further confirmed by the new results presented in this work. The role of the edge-peeling response in ELM suppression is less exploited in the previous work and is therefore one of the focusing points in this study.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Such a correlation has previously been obtained in the modelling of several tokamak devices 4,7,8,13,25 and will be further confirmed by the new results presented in this work. The role of the edge-peeling response in ELM suppression is less exploited in the previous work and is therefore one of the focusing points in this study.…”
Section: Introductionsupporting
confidence: 88%
“…In particular, the fluid model predicted optimal coil phasing, which maximizes the edge-peeling response, agrees well with the best achievable ELM mitigation in experiments. 33 This is confirmed by MARS-F, [10][11][12] NEMEC, 4 and JOREK 13 computations. In particular, systematic scans with varying edge safety factor 12,37 as well as plasma pressure 37 yield simple analytic fitting formulas for the optimal coil phasing, with varying plasma conditions.…”
Section: Modelling Elm Mitigation Experimentssupporting
confidence: 57%
See 1 more Smart Citation
“…The parameters used are similar to the one described in Ref. [21] and reproduce as accurately as possible the experimental situation. The main limitations of the modeling are the increased central resistivity η 0 = 8.1 × 10 −7 Ω.m (value one order of magnitude larger than the Spitzer value, but the T −3/2 e dependency is accounted for in the simulations, T e being the electron temperature) and the restriction of the simulations to the toroidal modes n ≤ 8 to limit their computational costs.…”
Section: A Experimental Configuration and Simulation Parametersmentioning
confidence: 99%
“…The electron perpendicular flow generate currents on resonant surfaces, which can induce a magnetic field opposite to the applied perturbation, resulting in a zero net perturbation penetrating in the plasma: RMPs are then screened. More recently, it was found that RMPs can also excite marginally stable peeling-kink modes at the plasma edge, capable to improve the RMP penetration [19][20][21].…”
mentioning
confidence: 99%